International Petroleum Technology Conference 2005
DOI: 10.2523/10727-ms
|View full text |Cite
|
Sign up to set email alerts
|

Steam Injection in Fractured Carbonate Reservoirs: Starting a New Trend in EOR

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractSignificant volumes of heavy oil remain in fractured carbonate reservoirs worldwide. Some of these reservoirs are good candidates for the application of thermally assisted gas-oil-gravity-drainage (TA-GOGD), a novel EOR technique. Unlike a normal steam flood, the steam is used as a heating agent only to enhance the existing drive mechanisms. The elegance of TA-GOGD is that the fracture network is both used for the distribution of steam (heat) and the recovery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Until the publication of this paper, only five steam pilots in fractured carbonates were reported: (1) the Lacq Superieur field, France, (2) the Ikiztepe field, Turkey, (3) the Qarn Alam field, Oman, , (4) the Yates field, U.S.A., and (5) the Bati Raman field, Turkey . The decision to go for a full field application was only made for the Qarn Alam project, and conversion to full field application is still in progress. …”
Section: Problem Statementmentioning
confidence: 99%
“…Until the publication of this paper, only five steam pilots in fractured carbonates were reported: (1) the Lacq Superieur field, France, (2) the Ikiztepe field, Turkey, (3) the Qarn Alam field, Oman, , (4) the Yates field, U.S.A., and (5) the Bati Raman field, Turkey . The decision to go for a full field application was only made for the Qarn Alam project, and conversion to full field application is still in progress. …”
Section: Problem Statementmentioning
confidence: 99%
“… Cyclic steam pilot in Cao-32 Field, fracture limestone heavy crude oil in China [179].  Steamflood pilot and recently announced full field implementation in Qarn Alam Field, Oman [18,[180][181][182]. Oman also announced steam injection project in limestone Fahud Field among other steam pilots [18].…”
Section: Thermal Methodsmentioning
confidence: 99%
“…In 1997, Al-Shizawi et al discussed the methods of heat monitoring in the same field for the same pilot project . Later studies on Qarn Alam showed the field application possibilities and the physics of steam injection. …”
Section: Introductionmentioning
confidence: 99%